2014
DOI: 10.3389/fphys.2014.00494
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the electromechanical delay and its components during voluntary isometric contraction of the quadriceps femoris muscle

Abstract: Electromechanical delay (EMD) was described as a time elapsed between first trigger and force output. Various results have been reported based on the measurement method with observed inconsistent results when the trigger is elicited by voluntary contraction. However, mechanomyographic (MMG) sensor placed far away on the skin from the contracting muscle was used to detect muscle fiber motion and excitation-contraction (EC) coupling which may give unreliable results. On this basis, the purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 35 publications
(67 reference statements)
6
75
0
Order By: Relevance
“…Muscle contractile properties are often measured under active voluntary control or by surface electrode induced potentials (electrically evoked). For active isometric muscle contraction, an electromechanical delay of 49.73 6 7.99 ms has been reported in the literature (14), but it was also reported that electrically stimulated contractions show a significantly shorter electromechanical delay than voluntary contractions (16). Furthermore, each muscular activity has a specific contraction and relaxation time that is probably dependent on the composition of muscle fiber types.…”
Section: Introductionmentioning
confidence: 92%
“…Muscle contractile properties are often measured under active voluntary control or by surface electrode induced potentials (electrically evoked). For active isometric muscle contraction, an electromechanical delay of 49.73 6 7.99 ms has been reported in the literature (14), but it was also reported that electrically stimulated contractions show a significantly shorter electromechanical delay than voluntary contractions (16). Furthermore, each muscular activity has a specific contraction and relaxation time that is probably dependent on the composition of muscle fiber types.…”
Section: Introductionmentioning
confidence: 92%
“…Torque signals were recorded at a sampling frequency of 4 kHz (PowerLab, AD Instruments, Australia) and were not filtered thereafter. Automated detection of EMG onset was first applied (threshold level: 3 SD) (Begovic et al, 2014). A 64-channel electrode array was positioned on the biceps femoris.…”
Section: Data Processingmentioning
confidence: 99%
“…EMG signals were band-pass filtered (10-400 Hz, 2 nd -order Butterworth filter), then Teager-Kaiser energy operator was applied to improve signal-to-noise ratio and minimize erroneous EMG onset detection (Solnik et al, 2010). Automated detection of EMG onset was first applied (threshold level: 3 SD) (Begovic et al, 2014). Among all channels, the five fastest channels were visually inspected and only the first onset of EMG was retained for further analysis.…”
Section: Data Processingmentioning
confidence: 99%
“…Clinically, measurement of EMD has been used to examine the severity and progression of myotonic dystrophy and cerebral palsy, and Begovic et al . suggested that EMD along with ultrasound may be useful for tracking recovery from spinal/supraspinal injuries and to quantify these effects on the peripheral nervous system.…”
mentioning
confidence: 99%
“…Clinically, measurement of EMD has been used to examine the severity and progression of myotonic dystrophy 5 and cerebral palsy, 8 and Begovic et al 9 suggested that EMD along with ultrasound may be useful for tracking recovery from spinal/ supraspinal injuries and to quantify these effects on the peripheral nervous system. Using electrical stimulation, Orizio et al 5 showed that patients with myotonic dystrophy exhibited greater EMD from the tibialis anterior than healthy controls due to elongated time durations associated with excitation-contraction coupling and the series elastic component.…”
mentioning
confidence: 99%